(untitled) (Cadernos de Sociomuseologia, 2009)
The widening of the notion of heritage and the consequent redefinition of the “museological object”, the idea of community participation in the definition and management of the museological practice, museology as a development factor, the issues of interdisciplinarity, the use of “new technologies” of information and museography as an autonomous communications means, are examples of issues resulting from contemporary museological practices. If indeed museology in Portugal intends to continue to participate in international museology’s renovation process, it is evident that it must adequately (re)think theoretical and practical museology so as to meet the new demands…